Аппаратно-программный комплекс для электромиостимуляции и лечения фантомных болей - Левенец, А. С.; Подпружников, П. М.; Шабанов, Е. С. (ХНУРЭ, 2008)
Electrostimulation - application of an-electric current for the purpose of excitation or strengthening of activity of certain bodies and systems. Phantom pains one of the most mysterious phenomena in medicine. The similar phenomenon is observed approximately at two thirds of the patients who have passed through amputation. In most cases phantom pains pass in finitenesses by itself. But sometimes they become chronic and is intolerable by the strong. Experts cannot explain till now, than the phenomenon of phantom pains in finitenesses is caused. Nevertheless there are ways to relieve a pain, one of them is the irritation a weak pulse current of low frequency of skin receptors on healthy finiteness in those places where there is a phantom. The hardware-software complex has been developed for electrostimulation and treatment of phantom pains which consists of the stationary electrostimulator, the special software and an individual portable electrostimulator.
Keywords: электромиостимуляция; биомединженерия